Structure and spatio-temporal dynamics of the artisanal small-scale fisheries at the future MPA of “Taza” (Algerian coast, SW Mediterranean) - BOUBEKRI, IBRAHIM; CAVEEN, ALEX JAMES; DJEBAR, ABDALLAH BORHANE; AMARA, RACHID; MAZUREK, HUBERT (Mediterranean Marine Science, 2018)
Artisanal Small-Scale Fisheries (SSFs) are a primordial and very diverse activity in the Mediterranean, also within Marine Protected Areas (MPAs). This diversity is explained in terms of target species, gears, and fishing strategies. The main objective of this work was to investigate the spatio-temporal dynamics of artisanal SSFs of the future MPA of “Taza” (Algeria, SW Mediterranean). Data were collected through direct assessment of daily landings and using questionnaires. They were the subject of multivariate analyses that allowed us to identify the métiers practiced by artisanal fishers. During the one year (May 2013 to April 2014) field work period, 1330 fishing trips and 1613 fishing operations in 16 fishing grounds were recorded in the Ziama fishing harbor, where 15.2 tons of total catch was assessed. Our results show that, in the study area, the boats are predominantly gillnetters and that among the five métiers characterized by target species, gear type, fishing grounds, and fishing seasons, two métiers (“Mullus surmuletus trammel net” and “Sparids monofilament gillnet”) are practiced throughout the year, while the remaining three (“Sarda sarda driftnet”, “Merluccius merluccius set gillnet”, and “Pagellus set gillnet”) are specific to a determined period of the year. The ‘Mullus surmuletus trammel net’ métier represents 40% of the total fishing operations, of which 57.5% are carried out in the coastal sector at - 25 m. This study could contribute to defining the appropriate management approaches for SSFs in the future MPA of “Taza” by providing baseline information to build a sound management plan. In Algeria, it will certainly serve as a scientific reference in terms of zoning, protection of biodiversity, and specific monitoring at particular locations and periods of the year for the sustainable management of MPAs.